Modelo de dimensionamento de geradores síncronos com ímãs permanentes de superfície utilizando ímãs de ferrite - Dembinski, Fabio Eduardo (2018)
This work proposes the use of an analytical sizing model to determine the main geometric dimensions of a synchronous generator with permanent surface ferrite magnets. Firstly, some of the tax conditions proposed by the State to encourage the use of renewable energy are mentioned, followed by a brief presentation of the principles of synchronous generators. Some generator topologies for wind micro-generation are also indicated, as well as the design parameters of rotating electric machines and the initial design model itself. In addition to describing the analytical method of design used, the characteristics of the computational program for field calculation, called EFCAD, were also shown succinctly, which served as a tool for project analysis. Finally, the results and techniques adopted for project improvement are presented. After an initial design, subsequent designs were obtained as a consequence of the introduction of techniques that sought to improve performance or introduce constraints on the size of the designed machine. Thus, four designs were obtained, for each of which the value of fem, the value of the respective synchronous inductance, and the value of the voltage at full load were analyzed by means of a finite element analysis software.